Analisis Neraca Massa Proses Pembuatan Virgin coconut oil dari Santan Menggunakan Metode Pemanasan (Hot Process) - Astuti, Nining Pambudi; Ferdian, Muh Agus; Rahman, Labib Hilia; Andini, Ulfa Putri; Jebarut, Hilairus; Firdausy, Kabata Imanda Tahta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Virgin coconut oil produced from coconut milk is a high value-added product in the coconut agro-industry, but small-scale processes are rarely analysed quantitatively, so opportunities to improve yield and reduce material losses remain insufficiently defined. This study aimed to establish and analyse a mass balance for the production of virgin coconut oil from coconut milk using a heating (hot process) method that represents micro- and small-scale operations. The methodology was developed as a case study based on a worked example of a single process cycle. A full mass balance was derived for the entire sequence, starting from the extraction of thick and thin coconut milk from 2.65 kilograms of grated coconut with the addition of 2.25 kilograms of water, followed by initial filtration, heating and separation of oil, water, and blondo, removal of residual water, reheating of the oil, and final filtration. All streams were classified as main product, co-products, aqueous phase, water vapour, and mechanical losses. The results show that the process produced 0.50 kilograms of virgin coconut oil, corresponding to a yield of 12.99 percent relative to the coconut milk feed and 18.87 percent relative to the grated coconut. With a theoretical oil content of 0.57 kilograms in the coconut milk, this corresponds to an oil recovery of 87.72 percent, while approximately 12 percent of the potential oil remained entrapped in blondo, filter residues, and press cake. The aqueous phase reached 2.75 kilograms, the process solids 0.49 kilograms, the final extraction residue 0.90 kilograms, water vapour 0.06 kilograms, and total losses 0.20 kilograms. This mapping reveals critical loss points at the extraction and separation stages and highlights the potential for valorising liquid and solid co-products as additional sources of value. Overall, the study demonstrates that applying a mass balance provides a sharp picture of efficiency and loss patterns in the production of virgin coconut oil from coconut milk by a heating method, and offers a quantitative basis for designing more efficient processes, reducing food loss and waste, and developing co-product utilisation strategies in small-scale coconut agro-industry.